The interplay among HIV, monocytes/macrophages, and extracellular vesicles: a systematic review. Issue 3 (10th January 2023) - Adhikari, Romin; Witwer, Kenneth W; Wiberg, Kjell J; Chen, Yun-Chi
Abstract: Despite effective antiretroviral therapies, chronic inflammation and spontaneous viral "blips" occur in HIV-infected patients. Given the roles for monocytes/macrophages in HIV pathogenesis and extracellular vesicles in intercellular communication, we performed this systematic review to delineate the triad of HIV, monocytes/macrophages, and extracellular vesicles in the modulation of immune activation and HIV activities. We searched PubMed, Web of Science, and EBSCO databases for published articles, up to 18 August 2022, relevant to this triad. The search identified 11, 836 publications, and 36 studies were deemed eligible and included in this systematic review. Data were extracted for the characteristics of HIV, monocytes/macrophages, and extracellular vesicles used for experiments and the immunologic and virologic outcomes in extracellular vesicle recipient cells. Evidence for the effects on outcomes was synthesized by stratifying the characteristics by outcomes. In this triad, monocytes/macrophages were potential producers and recipients of extracellular vesicles, whose cargo repertoires and functionalities were regulated by HIV infection and cellular stimulation. Extracellular vesicles derived from HIV-infected monocytes/macrophages or the biofluid of HIV-infected patients enhanced innate immune activation and HIV dissemination, cellular entry, replication, and latency reactivation in bystander or infected target cells. These extracellular vesicles could be synthesized in the presence of antiretroviral agents and elicit pathogenic effects in a wide range of nontarget cells. At least eight functional types of extracellular vesicles could be classified based on the diverse extracellular vesicle effects, which were linked to specific virus- and/or host-derived cargos. Thus, the monocyte/macrophage–centered multidirectional crosstalk through extracellular vesicles may help sustain persistent immune activation and residual viral activities during suppressed HIV infection. Abstract : HIV–monocyte/macrophage interactions take center stage in multidirectional crosstalk for modulation of persistent HIV activities and immune activation through extracellular vesicles.